2022
DOI: 10.3390/biom12020148
|View full text |Cite
|
Sign up to set email alerts
|

Sulfurtransferases and Cystathionine Beta-Synthase Expression in Different Human Leukemia Cell Lines

Abstract: The studies concerned the expression of sulfurtransferases and cystathionine beta-synthase in six human leukemia cell lines: B cell acute lymphoblastic leukemia-B-ALL (REH cells), T cell acute lymphoblastic leukemia-T-ALL (DND-41 and MOLT-4 cells), acute myeloid leukemia—AML (MV4-11 and MOLM-14 cells), and chronic myeloid leukemia—CML (K562 cells). Reverse transcription-polymerase chain reaction (RT-PCR) and Western blot analysis were performed to determine the expression of thiosulfate sulfurtransferase, 3-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 46 publications
2
8
0
Order By: Relevance
“…The research results find consistency with our previous work by Jurkowska et al [27]. The expression of TST in MOLT-4 was practically absent, which aligns with the data presented in Figure 4.…”
Section: Cystathionine β-Synthase and Cystathionine Gamma-lyasesupporting
confidence: 93%
See 2 more Smart Citations
“…The research results find consistency with our previous work by Jurkowska et al [27]. The expression of TST in MOLT-4 was practically absent, which aligns with the data presented in Figure 4.…”
Section: Cystathionine β-Synthase and Cystathionine Gamma-lyasesupporting
confidence: 93%
“…Furthermore, our previous research aligns with these findings, as we discovered unchanged rhodanese expression in all examined AML (MOLM-14, MV4 cell lines) and CML (K562 cell line) cells. However, rhodanese was not expressed in T-cell Acute Lymphoblastic Leukemia (T-cell ALL) cell lines (DND-41 and MOLT-4) [27]. The results concerning the MOLT-4 cell line are consistent with the data presented on Figure 4.…”
Section: Thiosulfate Sulfurtransferase In Various Types Of Leukemiasupporting
confidence: 88%
See 1 more Smart Citation
“…Chronic myeloid leukemia (CML), also known as chronic myelogenous leukemia, is a myeloproliferative neoplasm that involves uncontrolled myeloid cell growth [1]. CML differs from other myeloproliferative neoplasms because of the BCR-ABL1 fusion gene and Philadelphia chromosome (Ph) caused by t(9;22) (q34.1;q11.2) [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Since the demonstration [ 24 ] that the H 2 S-producing enzyme CBS is overexpressed in colon cancer, and that it plays various cancer-cell-supporting roles (such as cytoprotection, proliferative effects, pro-angiogenic effects and others), this field has steadily expanded (as reviewed recently in [ 10 ]). In the current Special Issue, Wrobel’s group published two articles focusing on the expression patterns of various H 2 S-producing enzymes in a variety of commonly used cell lines, and identified some commonalities as well as important cell-type-differences [ 25 , 26 ]. Moreover, in a study utilizing a patient-derived xenograft model, our own group has demonstrated that those colon cancers that express higher levels of CBS, when implanted onto nude mice, proliferate faster and respond better to pharmacological CBS inhibition than those colon cancers that express low levels of CBS [ 27 ].…”
mentioning
confidence: 99%